Antibacterial Effect of Edible (Medicinal) Fungi and Its Research Progress in Food Anticorrosion and Preservation - Na PENG; Peng ZHAO; Xinyi CHAI (Shipin gongye ke-ji, 2022)
The research on anticorrosion and preservation of biotechnology using microbial sources has gradually become a hot topic. The antibacterial effect of edible (medicinal) fungi highlights its application potential in food anticorrosion and preservation. Compared with the physical and chemical methods, the biological preservative and preservation method using fungi active substances for food has the characteristics of safety, low cost, ideal effect, energy saving and environmental protection. In this paper, the bacteriostatic effects of edible (medicinal) fungi on common rotting microorganisms in food and the research progress in food preservative and preservation applications in recent years are reviewed, including the bacteriostatic effects of edible (medicinal) fungi fermentation broth or mycelium (extract) on bacteria and fungi in food respectively, and its application examples, existing problems and development prospects in food preservation. The antibacterial active substances produced by edible (medicinal) fungi have broad antibacterial spectrum and certain selectivity, which are applied to food preservation and anticorrosion. It not only protects the ecological environment, but also ensures the green security and meets the needs of social and economic development.